Lobaplatin Inhibits Prostate Cancer Proliferation and Migration Through Regulation of BCL2 and BAX. Issue 2 (4th June 2019) - Cao, Hongwen; Feng, Yigeng; Chen, Lei; Yu, Chao
Lobaplatin is a diastereometric mixture of platinum (II) complexes, which contain a 1, 2-bis (aminomethyl) cyclobutane stable ligand and lactic acid. Previous studies have showed that lobaplatin plays inhibiting roles in various types of tumors. However, the role of lobaplatin in prostate cancer remains unknown. Cell viability was detected by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide assay. Cell proliferation was detected by cell colony formation assay. Cell migration and invasion were determined by transwell migration and invasion assay. Cell apoptosis was detected by flow cytometry. The messenger RNA and protein expression levels were detected by quantitative real-time polymerase chain reaction and Western blot. Lobaplatin treatment inhibits cell viability, cell proliferation, cell migration, and invasion, while promotes cell apoptosis of prostate cancer cell lines DU145 and PC3. Meanwhile, lobaplatin treatment regulates apoptosis by downregulation of BCL2 expression and upregulation of BAX expression levels. Our study suggests lobaplatin inhibits prostate cancer proliferation and migration through regulation of BCL2 and BAX expression.